Genome and transcriptome analysis of the basidiomycetous yeast Pseudozyma antarctica producing extracellular glycolipids, mannosylerythritol lipids. - Tomotake Morita; Hideaki Koike; Hiroko Hagiwara; Emi Ito; Masayuki Machida; Shun Sato; Hiroshi Habe; Dai Kitamoto (PLoS ONE)
Pseudozyma antarctica is a non-pathogenic phyllosphere yeast known as an excellent producer of mannosylerythritol lipids (MELs), multi-functional extracellular glycolipids, from vegetable oils. To clarify the genetic characteristics of P. antarctica, we analyzed the 18 Mb genome of P. antarctica T-34. On the basis of KOG analysis, the number of genes (219 genes) categorized into lipid transport and metabolism classification in P. antarctica was one and a half times larger than that of yeast Saccharomyces cerevisiae (140 genes). The gene encoding an ATP/citrate lyase (ACL) related to acetyl-CoA synthesis conserved in oleaginous strains was found in P. antarctica genome: the single ACL gene possesses the four domains identical to that of the human gene, whereas the other oleaginous ascomycetous species have the two genes covering the four domains. P. antarctica genome exhibited a remarkable degree of synteny to U. maydis genome, however, the comparison of the gene expression profiles under the culture on the two carbon sources, glucose and soybean oil, by the DNA microarray method revealed that transcriptomes between the two species were significantly different. In P. antarctica, expression of the gene sets relating fatty acid metabolism were markedly up-regulated under the oily conditions compared with glucose. Additionally, MEL biosynthesis cluster of P. antarctica was highly expressed regardless of the carbon source as compared to U. maydis. These results strongly indicate that P. antarctica has an oleaginous nature which is relevant to its non-pathogenic and MEL-overproducing characteristics. The analysis and dataset contribute to stimulate the development of improved strains with customized properties for high yield production of functional bio-based materials.